Enhancement of Students Cooperation Attitude through Traditional Game of Lompat Tali - Iip Istirahayu (JETL (Journal of Education, Teaching and Learning), 2020)
Character development in students is very important to be a better individual and understand the values that apply. Character development is done by instilling basic ethical values such as one of which is cooperation. The purpose of this research is to find out and analyze the increase in the value of cooperation of elementary school students in the city of Singkawang through the application of the traditional Lompat Tali game, as a form of preserving the nation's culture and building the nation's cultural character. The method used in this research is quantitative research. The study population was all elementary school students in Singkawang. Samples were selected using a purposive sampling technique as many as 50 groups. The type of data used in this survey research is quantitative data obtained from interviews, observations, and attitude scales. Analysis of the data in this study used the N-gain test to see an increase in student cooperation attitude. The results of the study based on the N-gain calculation show that the increase in the cooperative attitude of elementary school students is 0.38, which means that students of the traditional game of Lompat Tali can increase the cooperative attitude of elementary school students.